Pre & Post Merger Financial Analysis In PT Perusahaan Gas Negara Tbk and PT Pertamina Gas - Fitria Fitria; Hakiman Thamrin (Universitas Muhammadiyah Prof. DR HAMKA., 2022)
This study obtain financial performance differences of PT Perusahaan Gas Negara and PT Pertamina Gas before and after the merger in April 2018. Authors use state-owned companies in the Energy and Oil and Gas sector as population. The sampling technique was carried out using purposive sampling with the criteria for merging until 2019. SOE Financial Health Assessment method by KEPMENBUMN NO 100 and Pre-test & Post- tests using nine indicators : ROI, ROE, Cash Ratio, Current Ratio, TATO, TETA, Collection Period, Inventory Turn Over, and EVA. By using data two years before the merger (2016) until two years after the merger (2020), the results shows ROE changed after merger process, other indicators show variation results.